БУЛУТЛИ ТЕХНОЛОГИЯЛАР ДАРАЖАЛАРИ ВА ТАЪЛИМ ЖАРАЁНИНИ ВИРТУАЛИЗАЦИЯЛАШТИРИШ - Хожаниязова, С.П. (SCIENCE and SOCIETY, 2023)
This article discusses the possibilities of virtualization of the educational process based on the introduction of cloud technologies in the projection of individualization of work with students.
Keywords: cloud; technology; virtualization; services; platform